Chlamydomonas sp. as dynamic biorefinery feedstock for the production of methyl ester and ɛ-polylysine. (January 2019) - Sivaramakrishnan, Ramachandran; Suresh, Subramaniyam; Incharoensakdi, Aran
Graphical abstract: Highlights: The harvesting efficiency can be increased using FeCl3 flocculant. The in-situ transesterification using DMC produces methyl ester and glycerol carbonate. The sugars from spent biomass are utilized for the ɛ-polylysine production. Chlamydomonas sp. is a promising feedstock for the biorefinery approach. Abstract: An integrated production of methyl ester and ɛ-polylysine from Chlamydomonas sp. was studied using biorefinery approach. The harvesting efficiency of Chlamydomonas sp. was increased up to 92% by treatment with a flocculant FeCl3 at 100 mg/L for 30 min. The DMC (dimethyl carbonate) mediated enzyme catalyzed in-situ transesterification of Chlamydomonas sp. yielded the maximum methyl ester of 92% under optimized conditions. The valued-added product ɛ-polylysine was produced from hydrolysate obtained from the spent biomass of Chlamydomonas sp. using Streptomyces sp. The key components of sugar and MgSO4 used for ɛ-polysine production were optimized whereby the maximum ɛ-polylysine production was achieved at 50 g/L sugar and 0.3 g/L MgSO4 . The ɛ-polylysine production was further enhanced by supplementation of important amino acids (lysine and aspartate) and TCA cycle intermediates (citric acid and α-ketoglutaric acid). The maximum ɛ-polylysine production of 2.24 g/L was found with 4 mM citric acid supplementation after 110 h.